Socio-economic and ecological adaptability across South Asian Floodplains - Gurusamy, Balakrishnan Thanga; Vasudeo, Avinash Durgadas (Journal of Environmental Engineering and Landscape Management, 2023)
Flood Risk Potential across South Asian Floodplains corresponding to 2010 economic exposures had been reported to be about 11 billion US2012 and contributing more than 10% of Global values. Ecosystem approaches, based on Integrated Flood Management strategy of World Meteorological Organization, have been explored for balanced socio-economic and ecological adaptability enhancement, considering degradation of ecosystem services as fundamental issues and adaptation as optional solution. Adaptive Management methods have been explored for Flood Risk Minimization. General benefits of balanced socio-economic and ecological adaptation have been reviewed. Distributions of flood hazards, Gross Domestic Product, flood risk, Net Primary Productivity, carbon dioxide emissions and landscapes heterogeneity have been presented and analyzed for its influences over socio-economic and ecological adaptability. Distributions of Expected Annual Exposed socio-economic resources across 500 Years floodplains have been presented. Projected results corresponding to various two dimensional socio-environmental scenarios have been presented. Low Adaptable regions have been delineated.